1985
DOI: 10.1093/infdis/152.3.485
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Cell Wall of Haemophilus influenzae Type b by Transformation with Cloned DNA: Association with Attenuated Virulence

Abstract: A virulent strain of Haemophilus influenzae type b was used to construct a lambda library of chromosomal DNA in Charon 4, amplified in Escherichia coli. From this library a recombinant (I-69) phage was isolated that contained a 10.2-kilobase-pair fragment of DNA eliciting H. influenzae transformants whose colonies had a distinctive opaque phenotype. Compared with their H. influenzae parent strains the opaque I-69 transformants had two defined cell wall alterations: one in the lipopolysaccharide (greater mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…influenzae 1-69 Rd-/ b' is able to survive and multiply normally in vitro [4]. This shows that one (phosphorylated) dOclA in the lipopolysaccharide suffices for the survival of a gram-negative bacterium.…”
Section: Investigation Of the Unorneric 1inkuges In The Phosphorylutmentioning
confidence: 94%
See 3 more Smart Citations
“…influenzae 1-69 Rd-/ b' is able to survive and multiply normally in vitro [4]. This shows that one (phosphorylated) dOclA in the lipopolysaccharide suffices for the survival of a gram-negative bacterium.…”
Section: Investigation Of the Unorneric 1inkuges In The Phosphorylutmentioning
confidence: 94%
“…properties which are opposite to those found in the type-b-capsular, wildtype strains of H . injZuenzue [4]. This indicates that lipopolysaccharide is involved in modulating the virulence of H .…”
Section: Investigation Of the Unorneric 1inkuges In The Phosphorylutmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies on the H. influenzae mutant strain I-69 Rd ¹ /b þ (hereafter referred to as I-69) revealed that it contained a truncated LPS composed of lipid A and a single phosphorylated Kdo residue (Zamze et al, 1987). I-69 was identified from a genomic library of chromosomal DNA in a lambda vector when it was observed that transformants using DNA from one of the lambda clones produced an opaque phenotype (Zwahlen et al, 1985). Such transformants were found to be exquisitely sensitive to complement-mediated killing by serum and were defective in either colonizing the nasopharynx or causing invasive infections of infant rats.…”
Section: Introductionmentioning
confidence: 99%